Efektivitas Program Intervensi Pencegahan Kanker Serviks pada Remaja Putri Di Lingkungan SMK BIM Jombang: EFFECTIVENESS OF CERVICAL CANCER PREVENTION INTERVENTION PROGRAM FOR ADOLESCENT GIRLS IN SMK BIM JOMBANG ENVIRONMENT - Arfan, Nurul Azmi; Nuzula, Rizka Firdausi; Ningsih, Dovi Dwi Mardiyah (LPPM STIKes Bahrul Ulum Jombang, 2024)
Cervical cancer is one of the main causes of death in women throughout the world, including in Indonesia. Early prevention through education and health interventions is important to reduce the death rate from cervical cancer. This study aims to evaluate the effectiveness of a cervical cancer prevention intervention program in adolescent girls. The research method used was quasi-experimental with a pretest-posttest design without a control group. A total of 200 young women at secondary schools in SMK BIM Jombang were selected as respondents. The intervention provided included lectures, group discussions, distribution of educational materials, and counseling by competent health workers. Data was collected through a questionnaire that included the level of knowledge and awareness of young women about cervical cancer prevention before and after the intervention. The research results showed a significant increase in the level of knowledge and awareness of young women after the intervention. Before the intervention, 30% of adolescent girls had low knowledge, 55% had medium knowledge, and 15% had high knowledge. After the intervention, this percentage changed to 5% for low knowledge, 30% for medium knowledge, and 65% for high knowledge. In the aspect of awareness, before the intervention, 35% of young women had low awareness, 50% had moderate awareness, and 15% had high awareness. After intervention, 7.5% had low awareness, 32.5% had moderate awareness, and 60% had high awareness. This increase shows that the intervention program provided has succeeded in significantly increasing the understanding and awareness of young women. The involvement of parents and teachers provides additional support that is very important for applying the knowledge they gain in everyday life. In addition, policies that support cervical cancer prevention programs are needed to create an environment that supports the health of adolescent girls. Key Word : cervical cancer, adolescent girls, intervention programs, knowledge, awareness, health education.